SIMULATION STUDY ON THE EFFECT OF COAL SEAM DIP ANGLE ON DRUM WORK PERFORMANCE - MAO Jun; LIU XinYan; CHEN HongYue; SONG QiuShuang (Jixie qiangdu)
To study the interaction mechanism of shearer and the surrounding rock,using the MG500/1180-WD shearer model as research objects,EDEM discrete element simulation software is used to establish the three-dimensional simulation model,Considered the effect of the factor which is coal fragmentation and roof pressure on the performance of shearer cutting. Study on the dynamic process of shearer cutting.Using single-factor method to study the effect of coal seam dip angle on the factor of coal loading rate、cutting resistance and special energy consummation for cutting. Study on the wear of cuttings under different working conditions. The results show that when the dip angle is in the range of 0 ° ～ 10 ° in the range of-20 ° ～ 0 °, the effect on the working performance of the shearer is small, which can satisfy the coal loading efficiency of the shearer. Cutting stability. When the absolute value of the dip angle is large, the inclination angle is negative or the absolute value is large, it has a significant effect on the working performance of the shearer. It may be considered to change the working parameters of the shearer, such as reducing the drum speed, Speed, adjust the cutting depth to improve the performance of coal miners, in order to achieve efficient cutting shearer provides an improved reference.